Trust of second-generation immigrants: Intergenerational transmission or cultural assimilation? - Julie Moschion; Domenico Tabasso (IZA Journal of Migration, 2014)
This paper studies the respective influences of intergenerational transmission and the environment in shaping individual trust. Focusing on second generation immigrants in Australia and the United States, we exploit the variation in the home country and in the host country to separate the effect of cultural transmission from that of the social and economic conditions on individual trust. Our results indicate that trust in the home country contributes to the trust of second generation immigrants in both of the host countries, and marginally more in the United States. Social and economic conditions in the host country also affect individual trust.
Keywords: J15; O15; Z10; 330; Trust; Migration; Culture